Wild mushrooms of Lulung, Similipal Biosphere Reserve, Odisha, India: Food and Medicinal aspects - Kulkarni, Supriya; Joshi, S.; Kumar, M.; Nayak, S. K.; Kumar, Sanjeet; Thatoi, H. N. (Indian Forester, 2025)
Covid-19 readdresses the value and utilization of the nutraceutical to provide food and medicinal stuffs and to boost immunity. In these aspects, researchers globally searching wild source for existing traditional nutraceutical. Keeping these in view, an attempt has been made to collect the edible, medicinal and nutraceutical wild mushrooms from the Lulung area of Similipal Biosphere Reserve (SBR), Odisha. Extensive field survey was made to collect the desired information through questionnaire from tribal communities of study areas. Forty species were enumerated belonging to 28 genera and 22 families. Out of these, 24 species were edible and the rest species have either medicinal, toxic, or not evaluated for their potential.